The Quality of Oceanographic Parameters in the Waters of Setan Island, West Sumatra - Sipahutar, Alan Nuari; Rifaldi, Rifardi; Mubarak, Mubarak (Jurnal Perikanan dan Kelautan, 2024)
This research was conducted from February to March 2023 in Setan island, West Sumatra. This study aimed to determine the sediment accumulation rate and coral cover, as well as the correlation between sediment accumulation rate and coral cover. The survey method was used in this research. The sediment accumulation rate was measured using a sediment trap. At the same time, the coral cover was observed using the underwater photo transect (UPT) method with a transect length of 50 m. The total suspended solid was analyzed using the Gravimetric method. Observations were made at four sampling points at depths of 3 and 6 m. The sediment accumulation rate at a depth of 3 m ranged from 0.946315 to 1.534992 mg/cm²/day, while at a depth of 6 meters, it ranged from 1.357756 to 1.607786 mg/cm²/day. The percentage of live coral cover at a depth of 3 meters ranged from 3.40% to 31.36%, and at a depth of 6 m, it ranged from 0.33% to 30.50%. The total suspended solids values ranged from 23 to 96 mg/L. Regression analysis showed that the sediment accumulation rate negatively influenced the percentage of live coral cover.